2009
DOI: 10.1002/eji.200839156
|View full text |Cite
|
Sign up to set email alerts
|

MYD88‐dependent and ‐independent activation of TREM‐1 via specific TLR ligands

Abstract: Triggering receptor expressed on myeloid cells (TREM)-1 plays an important role in myeloid cell-activated inflammatory responses. Although TLR ligands such as LPS and lipoteichoic acid have been shown to upregulate TREM-1 expression in macrophage and neutrophils, the role of specific TLR in inducing the expression of TREM-1 remains unclear. In this study, we investigated whether the presence of TLR is necessary for the expression of TREM-1. We show that BM-derived macrophages from TLR4 and TLR2 KO mice failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 43 publications
2
41
0
3
Order By: Relevance
“…TREM-1 elevated the expression of TLR2, TLR4, and MyD88, while TLR5 and TLR9 expression was not affected (data not shown). Interestingly, other studies have demonstrated that TREM-1 expression is enhanced by activating TLR2 and TLR4 but not TLR3, TLR7/8, or TLR9 (23,43,44). Taken together, these findings suggested that TREM-1 may be associated with TLR2 and TLR4 but not other TLRs.…”
Section: Discussionmentioning
confidence: 72%
“…TREM-1 elevated the expression of TLR2, TLR4, and MyD88, while TLR5 and TLR9 expression was not affected (data not shown). Interestingly, other studies have demonstrated that TREM-1 expression is enhanced by activating TLR2 and TLR4 but not TLR3, TLR7/8, or TLR9 (23,43,44). Taken together, these findings suggested that TREM-1 may be associated with TLR2 and TLR4 but not other TLRs.…”
Section: Discussionmentioning
confidence: 72%
“…5,[26][27][28] The regulation of TREM-1 by these Pattern recognition receptors (PRRs) is independent of MyD88 but TRIF-dependent, 29 and involves transcription factors NFκB (p65), PU.1 and AP1. 30 Co-engagement of PRRs and TREM-1 results in higher cytokines production than the sum of the responses of either TREM-1 or PRRs alone.…”
Section: Trem-1 Structure and Functionmentioning
confidence: 99%
“…Previous studies showed that LL-37 inhibits inflammatory cytokine production in response to LPS through the downregulation of p38 MAPK and NFκB signaling pathways [11,14,63,64]; similar mechanisms may be responsible for the antagonistic effects of LL-37 on TREM-1 expression in response to LPS or LTA. It was recently reported that upregulation of TREM-1 by LPS is mediated through a signaling pathway dependent on the adapter protein TIR-domain-containing adapterinducing interferon-β (TRIF) while its upregulation by LTA is mediated by MyD88 [65]. The ability of LL-37 to inhibit TREM-1 induction by both LPS and LTA therefore suggests that modulation of both MyD88 and TRIF-dependent TLR signaling responses is involved.…”
Section: Discussionmentioning
confidence: 98%